Pengaruh Laba Bersih, Hutang, dan Arus Kas Operasi Pada Kebijakan dividen dengan Ukuran Perusahaan Sebagai Variabel Moderasi (Studi Pada Perusahaan Manufaktur yang Terdaftar pada Bursa Efek Indonesia tahun 2020-2021) - Rocky Bernardito; Surya Raharja (Jurnal Akuntansi dan Pajak, 2023)
Dividend policy is the company's policy in determining how much profit will be paid as dividends to investors. Optimal dividend policy needs to be considered because it can create a balance between the current dividend and growth in the next period. The purpose of this study was to determine the effect of profit, debt and operating cash flow on dividend policy and the ability of company size to moderate the effect of profit, debt and operating cash flow on dividend policy of manufacturing companies listed on the IDX for 2020-2021 with purposive sampling as sample determination method. Companies that meet the criteria are 30 companies. Moderated Regression Analysis (MRA) was used to test the data in this study. The results obtained show that profit has a positive effect and debt has a negative effect on dividend policy, but operating cash flow has no effect on dividend policy. This study also found that company size can strengthen the effect of profit, debt, and operating cash flow on dividend policy Keyword: Profit; Debt; Operating Cash Flow; Company Size; Dividend Policy